2019
DOI: 10.1038/s41467-019-10157-5
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic framework membranes through a mixed-dimensional assembly for molecular separations

Abstract: Covalent organic frameworks (COFs) hold great promise in molecular separations owing to their robust, ordered and tunable porous network structures. Currently, the pore size of COFs is usually much larger than most small molecules. Meanwhile, the weak interlamellar interaction between COF nanosheets impedes the preparation of defect-free membranes. Herein, we report a series of COF membranes through a mixed-dimensional assembly of 2D COF nanosheets and 1D cellulose nanofibers (CNFs). The pore size of 0.45–1.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
182
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(183 citation statements)
references
References 72 publications
1
182
0
Order By: Relevance
“…[255] To promote the sieving effects and mechanical strength of COF membranes, 1D cellulose nanofibers (CNFs) were integrated into the membrane (Figure 12c). [247] The pore size (0.45-1.0 nm) that rendered membrane precise molecular sieving ability was obtained. Owing to the hydrogen-bonded parallel chains and abundant hydroxyl groups, the nanocomposites exhibited elevated membrane stability.…”
Section: Desalinationmentioning
confidence: 93%
“…[255] To promote the sieving effects and mechanical strength of COF membranes, 1D cellulose nanofibers (CNFs) were integrated into the membrane (Figure 12c). [247] The pore size (0.45-1.0 nm) that rendered membrane precise molecular sieving ability was obtained. Owing to the hydrogen-bonded parallel chains and abundant hydroxyl groups, the nanocomposites exhibited elevated membrane stability.…”
Section: Desalinationmentioning
confidence: 93%
“…However, since Yaghi's landmark paper in 2005, research in this field had been mainly focused on the design and synthesis of new COF structures intending to increase the surface area and pore volume . For this reason, more recent studies concerning COF applications have become an active area of research in organic chemistry …”
Section: Introductionmentioning
confidence: 99%
“…However, as far as size-dependent separation with COF membrane is concerned, it has been proved to be very difficult to accurately control the pore sizes in the sub-nm scale, either through control of monomer size or through pore modification [6][7][8] . Recently, Yang et al 35 reported several COF membranes with sub-nm pores prepared by vacuum filtration using 2D COF nanosheets and 1D cellulose nanofibers (CNFs) as starting materials. Due to the shielding effect of CNFs, the aperture of obtained COF-based membrane is in the range of 0.45-1.0 nm.…”
mentioning
confidence: 99%